SYNTHESIS AND CHARACTERIZATION OF NOVEL CHIRAL (1R,2R)-1,2-BIS[5-(AMINOMETHYLPHOSPINIC ACID)-1,3,4-THIADIAZOL-2-YL]ETHANE-1,2-DIOLS - Koparir, P.; Karaarslan, M.; Orek, C.; Koparir, M. (Taylor & Francis Ltd, 2012)
(1R,2R)-1,2-bis[5-(arylideneamino)-1,3,4-thiadiazol-2-yl]ethane-1,2-diol (2a-d) were synthesized by using appropriate aldehydes and (1R,2R)-1,2-bis(5-amino-1,3,4-thiadiazol-2-yl)ethane-1,2-diol (1) as a starting compound. Then, the phosphinic acid component (3a-d) were obtained from (2a-d) and hypophosporus acid. In addition, the structures of the novel chiral compounds (2a-d) and (3a-d) were confirmed by elemental analyses, IR, H-1-NMR, C-13-NMR, and P-31-NMR spectra. H-1 NMR and C-13 NMR spectra for 1, 2a, and 3a (Figures S1-S6) are available online in the Supplemental Materials.
Keywords: 1,3,4-Thiadiazole; aminophosphinic acid; tartaric acid; ethane-1,2-diol